UPAYA WORLD WIDE FUND FOR NATURE (WWF) DALAM MENGATASI PERDAGANGAN PENYU ILEGAL DI PORVINSI BALI TAHUN 2008-2013 - Molisa Teresa Pardede; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes the role of WWF in deadling turtle trade in Bali. The study also describes the condition of the turtle trade in Bali. WWF is one of the leading conservation organization in the independent world, which is committed to the community and government leaders in Bali. Turtle has been listed as an Appendix I species (endangered) in CITES, yamg means all commercial trade in animals or part of the body is also prohibited. Data collection techniques used in this research is a case study in linking theory with data obtained through library research. Data obtained from books, journals, magazines, newspapers and other sources (analysis of documents). I also use the internet facility in the process of data collection related and relevant to the issues discussed in this study. The author uses the theory to explain the role of international organizations and the theory of pluralism. The conclusion of this study found that the WWF has been monitoring the turtle trade in Bali. WWF also tried to connect and engage all stakeholders in addresing turtle trade in Bali. Training and education for the public and the actors involved in engaging in the trade and use of tiger. WWF has been working closely with government agencies, as well as the surrounding environment to help organizations overcome the turtle trade. WWF turtle managed to reduce lavel of through support for education, law, and also help in the campaign progressed turtle trade in Bali. Keywords: WWF, Bali, turtle trade, CITES